Kalanchoe krigeae (K. subg. Kalanchoe; Crassulaceae subfam. Kalanchooideae), a new, small-growing species from northeastern South Africa split off from K. rotundifolia - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2023)
A new species of Kalanchoe (Crassulaceae subfam. Kalanchooideae), K. krigeae, is described from the Mpumalanga province in northeastern South Africa. Virtually the entire natural geographical distribution range of the species falls within the species-rich Wolkberg Centre of Endemism, to which it is near-endemic. In terms of vegetative morphology, especially its lanceolate-cymbiform to narrowly oblong-terete leaves, K. krigeae is similar to the recently reinstated K. decumbens, but its leaves are generally firmer and broader, and the natural geographical distribution ranges of the two species are separated by about 500 km. Kalanchoe krigeae further differs markedly from K. rotundifolia, which generally has an overall leaf shape that varies somewhat from nearly round to oblong-elliptic to elliptic-obovate. The new species differs from both K. decumbens and K. rotundifolia by being a light green to very light glaucous entity, while plants of K. rotundifolia are glaucous to dull light yellowish green and those of K. decumbens are generally uniformly light green. The reproductive morphology of K. krigeae is constant in terms of the size and shape of the corolla tube and lobes, with the distal part of the corolla tube and proximal part of the corolla lobes invariably becoming tightly twisted post-anthesis, as in K. decumbens and K. rotundifolia. Kalanchoe krigeae presents a combination of vegetative and reproductive morphological characters that warrants its recognition at species rank.